ANALISIS PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP CORPORATE RISK DISCLOSURE (CRD) (Studi Empiris pada Perusahaan-Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia) - Pramardhikasari, Ellensia; Januarti, Indira (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2018)
The purpose of this research is to provide empirical evidence about the factors which areinfluence corporate risk disclosure (CRD) in annual report of corporates mining. Corporatecharacteristics used in this research are firm size and leverage companies. Risk disclosure wasmeasured by content analysis-sentence approach. The research data were collected from 160of financial statements and annual reports of corporates mining that listed in Indonesian StockExchanges (IDX) for 2011 until 2015. Theory agency be used in this research to explains therelationship between variables. The analysis method of this research is using multipleregression analysis. The result of this research find that corporate characteristics, firm size,have significant positive effect on corporate risk disclosure (CRD) and leverage companiesdidn’t have significant effect on it.